Pengaruh Flash Sale dan Motivasi Belanja Hedonik terhadap Pembelian Impulsif di Marketplace Shopee pada Gen Z Kabupaten Tulungagung - Putri, Rini Anggia; Anasrulloh, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to determine the influence of Flash Sales and Hedonic Shopping Motivation on Impulsive Buying at the Shopee Marketplace in Gen Z, Tulungagung Regency. The method used is quantitative with an associative approach. Data was collected through a questionnaire distributed to 96 respondents, namely Gen Z in Tulungagung Regency. The results of the analysis show that there is a significant influence from Flash Sale on Impulsive Buying, with a calculated t>t table value of 3,724>1.986. Apart from that, Hedonic Shopping Motivation also has a significant effect on Impulsive Buying with a calculated t>t table value of 4.464>1.986. Simultaneously these two variables have a significant influence on Impulsive Buying with a calculated F value>F table 114.737>3.09. From the results of this research, it can be concluded that Flash Sales and Hedonic Buying Motivation can influence Impulsive Buying behavior on the Shopee Marketplace.